2021
DOI: 10.3390/jcm10102124
|View full text |Cite
|
Sign up to set email alerts
|

Smaller Intervertebral Disc Volume and More Disc Degeneration after Spinal Distraction in Scoliotic Children

Abstract: In recent decades, magnetically controlled growing rods (MCGR) were established to treat progressive early-onset scoliosis. The aim of this investigation was to assess the effect of long-term MCGR with continuous distraction on intervertebral discs in scoliotic children. Magnetic resonance imaging (MRI) of 33 children with spinal muscular atrophy was analyzed by grading intervertebral disc degeneration (IDD) and measuring intervertebral disc volume. Cohort I (n = 17) were children who had continuous spinal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The use of the SDS springs allows for increased loadsharing of the IVDs during periods of increased loading. Recent studies on “growth-friendly” implants have shown that IVDs within a distraction construct show a decrease in height and volume over time coincident with degenerative changes seen on MRI 20,21 . In the present model, the SDS IVDs were under more distraction during the first 6 months.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The use of the SDS springs allows for increased loadsharing of the IVDs during periods of increased loading. Recent studies on “growth-friendly” implants have shown that IVDs within a distraction construct show a decrease in height and volume over time coincident with degenerative changes seen on MRI 20,21 . In the present model, the SDS IVDs were under more distraction during the first 6 months.…”
Section: Discussionmentioning
confidence: 50%
“…Recent studies on ''growth-friendly'' implants have shown that IVDs within a distraction construct show a decrease in height and volume over time coincident with degenerative changes seen on MRI. 20,21 In the present model, the SDS IVDs were under more distraction during the first 6 months. However, this effect reversed after the first TGR distraction, with the spanned IVDs in the TGR model under increasing amounts of distraction, whereas the IVDs in the SDS model were increasingly subjected to compressive forces again.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recently, there have also been several studies suggesting an important role of the intervertebral disc in the treatment of early onset scoliosis with traditional growing rod distractions. 27,28 These radiological studies have shown (in 2D and 3D) that epiphyseal growth with distraction-based growing rods, coincides with height-and volume loss of the intervertebral disc. The present study shows that in preadolescent normal growth, intervertebral disc volume increases while intervertebral disc height remains stable (thoracic) or increases somewhat (lumbar).…”
Section: Discussionmentioning
confidence: 96%
“…Literature concerning bone health in children and adolescents after treatment with GFSI is very limited. Morphometric changes of vertebral bodies and disks in such cases were analyzed by Hasler et al, Lippross et al, and Hell et all, reporting reduced vertebral body depth and height, as well as pedicle size, also accompanied by degenerated intervertebral disks with smaller volume 25–28 . Cognetti et al observed in their case report smaller pedicles on the side of the implanted growing rods 29 .…”
Section: Discussionmentioning
confidence: 98%